Protein Profile In Serum Of Air Breathing Fish, Channa Gachu (Ham) - M. V.GAIKWAD.,; P.M. DAVANE,; V.R.MORE,; SHAIKH F.K.,; JAIWAL B.V,; Y.K. KHILLARE, (International Journal of Pharma and Bio Sciences, 2012)
Electrophoretic profile of blood serum proteins of air breathing fresh water fish Channa gachua was examined. Total eleven protein bands with varying migration on 10% polyacrylamide gel were observed in native run. The slow migrating bands designated as Cg-1, has molecular weights 154.20 Da and moderate migrating bands i.e. Cg-2, Cg-3, Cg-4, Cg-5, Cg-6, Cg-7, Cg-8, Cg-9 have molecular weights 71.61, 63.13, 58.61 56.70, 54.09, 45.29, 42.24 and 35.62 Da respectively. Remaining two fast migrating bands i.e. Cg-10 and Cg-11 have low molecular weights i.e. 16.15 and 14.79 KDa respectively. This protein profile of serum did not alter in the presence of reducing agent i.e. 2-mercaptoethanol on 12% sodium dodyacylsulphate polyacrylamide gel (SDS-PAGE) suggesting that, these proteins consists of single polypeptide chains.